2008
DOI: 10.1007/s00384-008-0536-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bisacodyl on postoperative bowel motility in elective colorectal surgery: a prospective, randomized trial

Abstract: Background Postoperative ileus is a common condition after abdominal surgery. Many prokinetic drugs have been evaluated including osmotic laxatives. The data on colon-stimulating laxatives are scarce. This prospective, randomized, doubleblind trial investigates the effect of the colon-stimulating laxative bisacodyl on postoperative ileus in elective colorectal resections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 43 publications
2
62
0
4
Order By: Relevance
“…Bisacodyl significantly decreased time to first BM (P=0.001) compared with placebo but provided no benefit on VAS pain scores, opioid consumption, nausea and vomiting, or hospital LOS. 60 These results suggest that bisacodyl may accelerate GI recovery after BR; however, it would still need to be combined with other agents to effectively mitigate other morphine-related side effects or to reduce opioid consumption.…”
Section: Promotility Agentsmentioning
confidence: 93%
“…Bisacodyl significantly decreased time to first BM (P=0.001) compared with placebo but provided no benefit on VAS pain scores, opioid consumption, nausea and vomiting, or hospital LOS. 60 These results suggest that bisacodyl may accelerate GI recovery after BR; however, it would still need to be combined with other agents to effectively mitigate other morphine-related side effects or to reduce opioid consumption.…”
Section: Promotility Agentsmentioning
confidence: 93%
“…Oral magnesium oxide was demonstrated to promote postoperative bowel function in a double-blinded RCT in abdominal hysterectomy [160] and in reports from a well-established enhanced recovery program in colonic resection [1,161]. Another randomised trial in liver resection showed that oral magnesium enhanced the return of bowel function [162] [164]. There was no effect of bisacodyl on tolerance to solid food or LOSH.…”
Section: Summary and Recommendationmentioning
confidence: 99%
“…Artificial nutrition should be considered selectively in patients with DGE of long duration Evidence level Very low Recommendation grade Strong Stimulation of bowel movement There is no high-level evidence to support a specific motility-enhancing drug. A multimodal approach involving the use of oral laxatives such as magnesium sulphate or bisacodyl may induce early gastrointestinal transit after colonic resections [173,174]. Some protocols for fast-track pancreatic surgery have recommended the use of laxatives postoperatively [175].…”
Section: Summary and Recommendationmentioning
confidence: 99%